WOMEN'S PORTRAYALS IN THE COMIC BOOKS : A Visual Grammar of the Heroines' Portrayals in the Selected Comic Books Published by DC Comics and Marvel - Pratiwi, Sani Satya (2013)
This paper entitled "Women's Portrayals in the Comic Books (A Visual Grammar of the Heroines' Portrayals in the Selected Comic Books Published by DC Comics and Marvel)" is aimed at investigating how women, especially heroines are portrayed in the comic books and what the portrayals signify. The study is a qualitative study using the visual grammar theory proposed by Kress and van Leeuwen (2006) and the systemic functional linguistics theory proposed by Halliday (2004). The data are in the form of four online comics published by DC Comics and Marvel. The study finds that heroines are portrayed in negative and positive ways. The negative ways portray the heroines as sex symbols, the ones who sexually stimulate men's attention in their appearance, greedy, fragile (especially when the heroines play their character as alter ego). While, the positive ways portray the heroines as strong, brave, smart and impressive ones. The findings also show that no matter how strong the heroines, they are still in the subjection. abstrak Skripsi dengan judul "Women's Portrayals in the Comic Books (A Visual Grammar of the Heroines' Portrayals in the Selected Comic Books Published by DC Comics and Marvel)" ini bertujuan untuk mencari tahu bagaimana wanita, khususnya pahlawan wanita digambarkan dalam buku-buku komik serta makna dari penggambaran tersebut. Penelitian ini menggunakan metode kualitatif dengan mengaplikasikan teori visual grammar (Kress dan van Leeuwen, 2006) serta systemic functional linguistics (Halliday, 2004). Data yang digunakan dalam penelitian ini berupa komik daring yang diterbitkan oleh DC Comics dan Marvel. Hasil penelitian menunjukkan bahwa pahlawan wanita digambarkan melalui dua sisi: negatif dan positif. Sisi negative menggambarkan wanita sebagai symbol seks, orang yang menstimulasi rangsangan seksual pada pria melalui penampilan mereka, serakah, lemah, rapuh (khususnya ketika mereka sedang memainkan peran sebagai alter ego). Sedangkan sisi positif menggambarkan wanita sebagai makhluk yang kuat, pintar dan menarik. Hasil penemuan juga menunjukkan bahwa tidak peduli sekuat apapun pahlawan wanita digambarkan dalam komik, mereka tetap berada dalam 'penjajahan'.